The Influence of Information Technology Utilization and Internal Control Systems on the Quality of Financial Reports - Kova, Tania Bara; Zulkifli, Zulkifli (Institut Bisnis dan Informatika Kesatuan, 2025)
In the era of globalization and the Fourth Industrial Revolution, the advancement of Information Technology (IT) has progressed rapidly, significantly impacting both private and public sectors. Despite the numerous benefits offered by IT, its implementation and utilization in the public sector often face various challenges, including infrastructure limitations, human resource constraints, and a lack of commitment to technological development. This study aims to evaluate the effect of Information Technology usage and internal control mechanisms on the quality of financial reports at Government Health Facilities in Region X. A quantitative research approach was employed, involving the distribution of questionnaires to 64 employees of Government Health Facilities in Region X as the primary data source. The data collection process included measurement and statistical analysis to test the hypothesis, utilizing SPSS 25 software for Windows. The study’s findings reveal that the effective use of Information Technology has a positive and significant impact on the quality of financial reports. Similarly, the internal control system also positively and significantly influences financial report quality. Together, these two variables have a substantial impact on improving the quality of financial reports at Government Health Facilities in Region X. This study provides practical benefits by encouraging the optimization of Information Technology and the strengthening of internal control systems to enhance financial report quality.